Land use and impact on habitability in the Historic Center of Lima, 2024: Case study: Mesa Redonda - Vela Aguirre, Norberto (2026)
The incidence of land use on the habitability of Mesa Redonda located in the historic center of Lima is analyzed, using a convergent approach that combines three techniques: bibliographic review, in situ observation and opinions of involved actors. In this place, a spatial transformation generated by commercial growth is evident that ignores the social well-being and quality of life of the residents, causing dynamics of erosion, alteration, destruction, displacement and/or gentrification and conditioning the population's ways of life. mobility and socio-spatial integration.Finally, the intense and aggressive expansion of commercial use is generating serious urban disorder that ignores the historical and cultural value of the area, negatively impacting habitability. This situation deteriorates the quality of life and threatens residential permanence, eroding community ties and altering the identity of the place.